Arqueologías del ¿Futuro? : Cartografía estética aplicada a territorios específicos - Castillo Herrera, Claudia (2012)
Systematic study in Specific territories físicoculturales entities characterized by ethical and aesthetic qualities in its philosophical sense and formal sense respectively. These entities are organically integrated level cultural practices based on an autopoietic performativity with grades that are widely debated academically and / or through specific productions of contemporary visual arts. Mapping aesthetic proposal conforms to a body of art works and theoretical, in the exhibition history addressed by this study, form a constellation theme and procedural attachment to the modes of production in the visual arts. These nodules or modes are integrated to a network epistemological fascinating, in light of the selected art works are always so critical transparentized based, the latter, is also critical the state of the global and systemic, are notable changes or adjustments, so appropriate to the complexity and / or program unit that maneuver both ethical and aesthetic and social needs of its realization. The spatial unit addressed as specific territories constitute denoted by physical and political margins forming residual spaces adjacent, while containers underlying, marks and signs of resistance asystemic administrative facilitated by a lack of consistent quality to its residual margin as invisible "blind spots" often not even counted, like a colony of homeless “San Eugenio” in Santiago de Chile and intangible artifacts which were exposed in the work "Vagrancy Architecture" 2005 in the Museum Contemporany Art MAC UACH in Valdivia, Chile, for the same author. Marginal places and locations that make an interesting "live tank", a "living archive" of book and recreate necessary for reflection and unconcealed through, among others, the same corpus of this curatorship, and their counterpoints of works and authors that in the same study notes. Regarding his research methodology presented here has been incipiently systematized during the years 2011-2012 comprising specific art actions in a 14-kilometer coastline that stretches from the place called "Punta Brava" to "The Book of Curiñanco" on XIV Rivers Region, Chile. These actions are experiencing considerable confluence of contemporary artistic production both from critics and its tributaries bordering epistemological humanities also an interesting corpus of contemporary works, curatorial and site projects that contribute significantly to the construction of possible futures, from the visual arts in particular and to the economic and human sciences in general, lead to the inescapable debate challenge involved in the discussion localization studies/ globalization teory.